Effect of split Application of N,P and K on the growth and Flowering of Rose CV Happiness - Nirmala George (Department of Horticulture, College of Agriculture, 1989)
An experiment was conducted to study the effect of split application of N, P and K on the growth and flowering of rose plants. The experiment was laid out in factorial CRD with two replications. Three levels each of N, P and K applied at three different intervals were compared with one absolute control. The effect of split application of nutrients has been proved by the results of the present study. In general, the mean increase in plant height was not affected by various treatments. The treatment combinations did not influence the production of sprouts also. Higher levels of K application increased the number of flowers produced, whereas higher levels of N reduced the flower yield. Maximum number of flowers were recorded by treatment with 10 g N: 30 g P: 10 g k applied at 30 days interval (n1 P2 K2 t2). The longest flower shoot was produced by the treatment combination of 20 g n:30 g p: 5 g k applied at 45 days interval (n2 p2 k1 t3). All the treatments resulted in an increase in thickness of the flower shoot, and also the number of leaves in the flower shoot. Diameter of the flower was found to increase significantly with increase in N level. The treatment with 20 g N: 15 g P: 10 g k applied at 15 days intervals (n2 p1 k2 t1) recorded the maximum diameter for the flower. The treatments were not maximum diameter for the flower. The treatments were not found to be affective for increasing the petal number compared to control. Opening of the flower bud was delayed by an increase in the level of phosphorus and also by the application of fertilizer at longer intervals. All the treatments were found effective in increasing the flower life. The treatment combination of 10 g N: 45 g P: 15 g k applied at 45 days interval (n1 p3 k3 t3) recorded the maximum value for the flower life. Diameter of the flower was seen to be highly correlated with nitrogen application. Phosphorus application showed highest correlation with the mean life of flower. All the biometric characters under the study showed highly significant positive correlation among themselves and also with the application of potassium.